2014
DOI: 10.1248/bpb.b14-00311
|View full text |Cite
|
Sign up to set email alerts
|

Delamanid Does Not Inhibit or Induce Cytochrome P450 Enzymes <i>in Vitro</i>

Abstract: Delamanid is a new drug for the treatment of multidrug-resistant tuberculosis. Individuals who are coinfected with human immunodeficiency virus and Mycobacterium tuberculosis may require treatment with a number of medications that might interact significantly with the CYP enzyme system as inhibitors or inducers. It is therefore important to understand how drugs in development for the treatment of tuberculosis will affect CYP enzyme metabolism. The ability of delamanid to inhibit or induce CYP enzymes was inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 19 publications
0
26
1
Order By: Relevance
“…In these studies, delamanid did not change the pharmacokinetics of rifampin, isoniazid, or pyrazinamide (31). Delamanid and its metabolites have been reported to exhibit no or weak inhibition of CYP enzymes and no induction (23), and the effect of the activities of drug transporters was not noticeable in the present study. This may provide an explanation as to why there is an absence of a DDI with Rifater.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…In these studies, delamanid did not change the pharmacokinetics of rifampin, isoniazid, or pyrazinamide (31). Delamanid and its metabolites have been reported to exhibit no or weak inhibition of CYP enzymes and no induction (23), and the effect of the activities of drug transporters was not noticeable in the present study. This may provide an explanation as to why there is an absence of a DDI with Rifater.…”
Section: Discussioncontrasting
confidence: 42%
“…Delamanid is not metabolized by NADPH-dependent reactions, including those catalyzed by CYP enzymes, in human or animal liver microsomes (4). Also, delamanid was not found to have inhibitory effects on the metabolism of exogenous CYP substrate compounds by eight CYP isoforms (CYP1A2, CYP2A6, CYP2B6, CYP2C8/9, CYP2C19, CYP2D6, CYP2E1, and CYP3A), even at a concentration of 100 mol/liter, well above the therapeutic concentration (23). The delamanid metabolites were noted to inhibit some other CYP isoforms but only at concentrations much higher than those observed in human plasma after the administration of therapeutic doses.…”
mentioning
confidence: 90%
“…However, eight metabolites, including the abundant metabolite (R)-2-amino-4,5-dihydrooxazole derivative ], in human and animal plasma were detected and identified in the investigation for the in vivo pharmacokinetics and metabolism of delamanid, as described in the companion article (Sasahara et al, 2015) in this issue of Drug Metabolism and Disposition. The maximum plasma concentration of M1 was nearly half that of delamanid (0.32 mM versus 0.78 mM) following twice daily administration of 100 mg delamanid for 56 days (Gler et al, 2012;Shimokawa et al, 2014;Sasahara et al, 2015), suggesting that M1 is the major metabolite. On the basis of the chemical structure of M1, it is proposed that delamanid is cleaved directly at its 6-nitro-2,3-dihydroimidazo(2,1-b)oxazole moiety by some extrahepatic mechanism (Matsumoto et al, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…Delamanid did not induce CYP1A2, CYP2B6, CYP2C9 and CYP3A4 at concentrations up to 10 μmol/L. These results suggested that at estimated therapeutic concentrations, delamanid is not expected to cause clinically significant interactions with other drugs metabolised via CYPs [7,25].…”
Section: Pharmacokineticsmentioning
confidence: 78%